Pengaruh Think Talk Write Berbantuan Teori Jerome Bruner Terhadap Literasi Sains Siswa SD - Muslim, Mukhammad Arwani; Widodo, Wahono; Gunansyah, Ganes (CV. Kurnia Grup, 2025)
Science literacy skills are essential skills that need to be developed since elementary school level. However, students' achievement of science literacy is often not optimal, so innovation in learning models is needed. This study aims to analyze the effect of implementing the Think Talk Write (TTW) learning model integrated with learning stages according to Jerome Bruner's theory on the science literacy skills of fifth grade elementary school students. Learning in this study was implemented using a teaching module that carries the theme of local culinary specialties of Porong, namely